Mitral regurgitation prior to transcatheter aortic valve implantation influences survival but not symptoms. (1st February 2016) - Boerlage-van Dijk, Kirsten; Wiegerinck, Esther M.A.; Takama, Takuro; Koch, Karel T.; Vis, M. Marije; de Mol, Bas A.J.M.; Piek, Jan J.; Bouma, Berto J.; Baan, Jan
Abstract: Background: Current data about the impact of concomitant mitral regurgitation (MR) on outcome in patients who undergo transcatheter aortic valve implantation (TAVI) are conflicting. Our purpose was to analyze the clinical course of MR and to assess the influence of MR on survival and clinical status after TAVI. Methods: We included 375 consecutive patients who underwent TAVI. MR grade and NYHA class were determined before TAVI and at follow-up. Results: In total 171 patients (46%) had MR grade ≥ 2 at baseline and of these 29% improved to MR grade ≤ 1 after TAVI. MR grade ≤ 1 at baseline was present in 204 patients (54%) and of these 17% worsened to grade ≥ 2 after TAVI. Improvement of MR was associated with absence of atrial fibrillation (OR: 2.35, 95%CI: 1.17–4.71, p = 0.02). Worsening of MR was associated with moderate or more aortic valve regurgitation after TAVI (OR: 4.2, CI: 1.83–9.49, p = 0.001). NYHA class improved at follow-up. Baseline MR grade did not determine the degree of clinical improvement (MR grade ≤ 1: NYHA ≥ 3 from 67% to 17%; MR grade ≥ 2: NYHA ≥ 3 from 69% to 14%). Although patients with MR grade ≥ 2 at baseline improved symptomatically, this degree of MR was associated with reduced two year survival compared with patients with MR grade ≤ 1(mortality 37% vs 26%; HR 1.99; 95% CI 1.27–3.13; p = 0.003). Conclusion: In patients who undergo TAVI almost half have MR grade ≥ 2 prior to the procedure. TAVI had no influence on MR grade at follow-up. Although patients with MR grade ≥ 2 at baseline improved symptomatically after TAVI, concomitant MR at baseline significantly reduced two year survival. Highlights: In patients who undergo TAVI almost half have MR grade ≥ 2 prior to the procedure. Concomitant MR in TAVI patients is associated with reduced two-year survival. TAVI results in improvement of NYHA class in patients with MR grade ≥ 2 at baseline. Improvement of MR after TAVI was associated with absence of atrial fibrillation. Worsening of MR after TAVI was associated with aortic regurgitation after TAVI.